FATIGUE AS A HAZARDOUS FACTOR FOR FLIGHT SAFETY - M. L. Alexander; N. K. Irina (Научный вестник МГТУ ГА)
The main priority of any air company activity and the main condition for its development is the achievement of the highest flight safety level. Significant positive results in this area have been recently achieved, hence, the relative stagnation of indexes, reflecting the flight safety as a condition of air transport system, has been revealed. It has become evident that the present accident prevention philosophy seems to be exhausted, and at the current stage of development it doesn’t allow to make a breakthrough in the solution of all the problems, which air companies face in this respect. In the perspective to find new ways to solve the existing tasks, in 2011, International Civil Aviation Organization Council adopted fatigue risk management international standards as an alternative for the traditional approach to managing crewmember fatigue by prescribing limits on maximum daily, monthly and yearly flight and duty hours. It’s a well-known fact that state of fatigue has a special place among the functional states, which are professionally significant for airmen work and which are the key link in “man-aircraft-environment” system.In this article, fatigue is considered to be a risk factor that contributes to the formation and development of crew violations and errors in the process of piloting the aircraft. We have analyzed the characteristics and reasons leading to inflight fatigue and estimated its influence on crew performance, considering the interrelation between them. The article specifies the methods and techniques to measure pilots fatigue; besides it has been substantiated the necessity of fatigue risk management system development in airlines to effectively ensure the flight safety.